Penerapan Teknologi Sabo sebagai Penahan Laju Sedimentasi Pada Muara Danau Limboto - Ardian Alfianto; Shandy Cecilia; Banata Wachid Ridwan; Chitra Widyasani Surya Putri (JURNAL TEKNIK HIDRAULIK, 2020)
Lake siltation due to erosion and sedimentation in Limboto Lake has happened since 1932. Based on 2017 analysis, lake contriction reached 4,000 (88,81 hectares annually). So, Limboto is predicted to go extinct in 2031. Since 2017, sabo dam implementation includes a series of effort called ‘Limboto Lake Revitalization’ to retain sedimentation flow. This study aims to review and to compare existing data with latest primary data collected. Measurement of sedimentation potential volume is done using software WaTEM/SEDEM, sabo design, and sabo plan. Overall, sabo plan designed by Sulawesi II River Basin Office is sufficient to accommodate potential of erotion and sedimentation flow in Limboto, despite the hypothesis that sabo dam amount is lacking and structure is positioned unfit with sabo design standard. The review shows that based on accommodating capacity, it is not necessary to add structure in upstream river. On the other hand, based distance between structures, each river requires at least 1 additional structure. This study advises an additional of capacity surge to 1.111.537 cubic meters. Batulayar section has the biggest capacity of 193.662 cubic meters per year, while the smallest is located in Tabongo1 with a capacity of 11.031 cubic meters per year. Updating and scheduled sabo dam review are required.